(2x-y)-(3x+2y)=

Simple and best practice solution for (2x-y)-(3x+2y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-y)-(3x+2y)= equation:


Simplifying
(2x + -1y) + -1(3x + 2y) = 0

Remove parenthesis around (2x + -1y)
2x + -1y + -1(3x + 2y) = 0
2x + -1y + (3x * -1 + 2y * -1) = 0
2x + -1y + (-3x + -2y) = 0

Reorder the terms:
2x + -3x + -1y + -2y = 0

Combine like terms: 2x + -3x = -1x
-1x + -1y + -2y = 0

Combine like terms: -1y + -2y = -3y
-1x + -3y = 0

Solving
-1x + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
-1x + -3y + 3y = 0 + 3y

Combine like terms: -3y + 3y = 0
-1x + 0 = 0 + 3y
-1x = 0 + 3y
Remove the zero:
-1x = 3y

Divide each side by '-1'.
x = -3y

Simplifying
x = -3y

See similar equations:

| 25b^2+4=5 | | .5c-10=-4 | | (A+B)(A-B)=(A+B)(A+B) | | 5(3x-4)=6x+7 | | 7a-1=5a+11 | | 2x+7=71 | | -3x=-y+1 | | [2(7.7-7)+0.6]= | | n^2=-10n-16 | | 7p+25=4p+28 | | v^2+5v+9v+45= | | 4(3x-1)-(2x-5)+16=2(3x+1)+(2x-5) | | 15y+3=58 | | -9x-10x= | | y-4=-8(x-1) | | 3x^3+27x^2+9x=0 | | 5[10-(3+4)+1]=14 | | 5Xsquared=75 | | -10x+x= | | 9+5x=17+x | | -5x+150=3+0.05x^2 | | 10x^4-12xy-16y^4= | | -5(-2+n)=-35 | | 2x^2-10x+12x^2= | | 4x+3+2x=x-8 | | 2x^4-10x+12x^4= | | 12x^4-12x+12x^4= | | 8m-12=52 | | x*3.5=1.75 | | 10x^4-10x+10x^4= | | 10x^4-20x+16x^4= | | 10x^4-20x-16x^4= |

Equations solver categories